Archive, Affect, and History in Feminist Transregional Activism - Macón, Cecilia (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
In recent years, transregional feminism has made strong use of social networks in order to organize its demands. This article deals with the role of the transmission of affect in the circulation of the hashtag #WomenStrike and in the way this collective and transregional dialogue found its roots in the history of feminism, particularly in foundational correspondences, performances, and the works of art of its early stages. This circulation constitutes a “counterarchive of affect” whose main consequences are herein discussed.